Pemilihan Merek Nugget Terlaris pada Kios Unggas Wahidin Pasuruan dengan Metode AHP (Analityc Hierarchy Process) - Risma Rossidha; Enik, Sulistyowati (Jurnal Teknologi dan Manajemen Sistem Industri, 2024)
Determining the brand of the best-selling nugget product at the Unggas Wahidin Pasuruan Stall is very important to do, because determining the best-selling product brand can predict which product brands should be sent mostly to the Unggas Wahidin Pasuruan Stall. One way that can be done is by implementing a decision support system. There are several criteria and alternative options that will be applied or chosen in selecting the best-selling product brand. Data analysis uses the AHP (Analytical Hierarchy Process) method, which allows several criteria to be selected directly by stall employees. From the sales report in June 2024, four criteria were selected to be compared, namely price, taste, quality and packaging. Meanwhile, the alternatives chosen are the Fiesta, Champ, Akumo and Asimo brands. From the selected data, after calculations, the average price criteria was 0.056702, the average taste criteria was 0.29389, the average quality criteria was 0.554904 and the average packaging criteria was 0.094504. After comparing each alternative selected, the highest result was obtained, namely the Fiesta nugget brand, which was 0.51393.